Feelings experienced by postpartum women in achieving the first bath of the newborn in rooming - Clarissa Morganna Santos Silva; Janmilli da Costa Dantas; Francisca Marta de Lima Costa Souza; Richardson Augusto Rosendo da Silva; Thais Rosental Gabriel Lopes; Jovanka Bittencourt Leite de Carvalho (O Mundo da Saúde)
The bath of a newborn child generates the first care taken by the mother. Furthermore, it provides a series of exchanges and interactional adjustments between the mother and the child, general observation of physical and motor conditions. The study objective to investigate the feelings of mothers in achieving the first spray bath of the newborn in the rooming. This is a descriptive study with qualitative approach carried out in a maternity hospital in northeastern Brazil in 2013. The study was approved by the Research Ethics Committee under report number 14079113.0.0000.5568.It was found after analysis of 27 interviewed mothers, two categories related to the spray bath of the newborn. The feelings of happiness and fear. It follows that the first care given to newborns by mothers through the spray bath permeated antagonistic feelings of happi- ness and fear. The connection between the binomial is demonstrated by the joy of being taking care of her baby during the daily bath, as well as by the fear of having at hand a being still tiny and fragile given special care.